2023
DOI: 10.1039/d2sm01590k
|View full text |Cite
|
Sign up to set email alerts
|

Water–alcohol–TiO2 dispersions as sustainable ink

Abstract: Nanocrystalline titanium dioxide (TiO2) is a widespread multifunctional and environmentally friendly material that has numerous applications requiring micro- or nanofabrication or thin film deposition. In most cases, fabrication of titania...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…TiO 2 Functional Ink: The ink was prepared according to a previously reported protocol. [37,[56][57][58] Briefly, a titanium isopropoxide solution (16 mL in 12 mL of 2-propanol) was added dropwise to a nitric acid solution (0.7 mL in 100 mL of water) and heated to 70 °C under stirring. The mixture was further heated to 80 °C and kept for 1 h under continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…TiO 2 Functional Ink: The ink was prepared according to a previously reported protocol. [37,[56][57][58] Briefly, a titanium isopropoxide solution (16 mL in 12 mL of 2-propanol) was added dropwise to a nitric acid solution (0.7 mL in 100 mL of water) and heated to 70 °C under stirring. The mixture was further heated to 80 °C and kept for 1 h under continuous stirring.…”
Section: Methodsmentioning
confidence: 99%
“…[17,18] At another point, titanium dioxide has established itself as a material well suited for printing optical structures, owing to its high refractive index in the visible spectrum and high colloidal stability in various water-based dispersions. [35][36][37] Thus, in our study, we mainly implemented the previously reported approaches toward inkjet printing metal halide perovskite resonators [17,18] and TiO 2 waveguides. [35] The fabrication route is schematically illustrated in Figure 1a-c.…”
Section: Design and Fabrication Of Photonic Chipmentioning
confidence: 99%